Teologia da Aliança e sua relação com a dignidade humana: aspectos coincidentes entre a Nova Aliança e as principais celebrações da Aliança no Antigo Testamento - Surian, Francisco Emílio (2011)
Under the context of the Alliance, God acts by man and the man acts in the certainty of being an instrument in God's hands so that everyone's life is more worthy. How to bring this understanding of the Alliance well known in the Old Testament to the New Testament? This is the challenge proposed by this study in view of the fact that God's Alliance with the people always pointed to human dignity. The proposal for a Alliance of God with the people in these days might be uncomfortable, because under the humanity of the twenty-first century, the greatest technological development never seen before, lives together with the most degrading human misery. According to God, the dignity is for everyone, especially the last, for the poor, the outcast. Therefore it is imperative that the promise, the commitment and the symbol of God's Alliance with mankind to be revealed so that, once again, the human history re-finds the possibility of life in its fullness